2014
DOI: 10.2134/agronj14.0222
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Maturity Group Choices for Early and Late Plantings in the Midsouth

Abstract: Growing conditions in the U.S. Midsouth allow for large soybean [Glycine max L. (Merr.)] yields under irrigation, but there is limited information on planting dates (PD) and maturity group (MG) choices to aid in cultivar selection. Analysis of variance across eight (2012) and 10 (2013) locations, four PD, and 16 cultivars (MG 3-6), revealed that the genotype by environment (G×E) interaction accounted for 38 to 22% of the total yield variability. Stability-analysis techniques and probability of low yields were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 22 publications
9
61
2
1
Order By: Relevance
“…In our study we found that the duration of each of these periods was shortened and in turn, led to a decrease in cumulative radiation, precipitation, GDD, and average photoperiod; this is a similar finding to Salmerón et al. (). When precipitation and GDD accumulation decrease during the R3‐R7 period we see a significant decline in relative yield.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we found that the duration of each of these periods was shortened and in turn, led to a decrease in cumulative radiation, precipitation, GDD, and average photoperiod; this is a similar finding to Salmerón et al. (). When precipitation and GDD accumulation decrease during the R3‐R7 period we see a significant decline in relative yield.…”
Section: Discussionsupporting
confidence: 92%
“…In that study, planting occurred earlier in spring and later in the summer by up to 40 d compared to the variety trial data we used. However, our results are within the optimum MG ranges (MGs that exhibited the highest yields) that were identified across Missouri, Arkansas, Tennessee, Mississippi, Louisiana, and Texas (Salmeron et al, 2014). It should be noted that across these states, our data included more than 450 environments (location × year) with multiple MGs, and many varieties tested within each environment.…”
Section: Resultssupporting
confidence: 70%
“…In favorable weather conditions and in regions where planting dates can be flexible, such as in the southern states, earlier or later maturing varieties than the optimum can also be successfully grown. This has been observed in a study conducted at several locations in the southern United States where early and late planting dates for the specific locations were tested (Salmeron et al, 2014). In that study, planting occurred earlier in spring and later in the summer by up to 40 d compared to the variety trial data we used.…”
Section: Resultsmentioning
confidence: 63%
“…Finally, early planting (Bastidas et al, 2008;Salmerón et al, 2014;Wilcox and Frankenberger, 1987) and warm early spring temperatures (Cooper, 2003) induce earlier flowering, lengthen the reproductive period, and increase solar radiation interception and BAR during seedfilling. Rowntree et al (2014) compared early (∼May 1) and late (∼June 1) planting dates for 57 MG 3 cultivars released between 1923 and 2008 and found that the rate-of-yield increase was 23% greater (1.74 vs 1.41 kg ha −1 yr −1 ) for the earlyplanted treatment than the late-planted treatment.…”
Section: Management For Reaching Potential Yieldmentioning
confidence: 99%